Tipu Daya Wanita dalam Kisah Nabi Yusuf dan Nabi Sulaiman Perspektif Tafsir Al-Mishbah - Nadhira, Athifia Austrin; Akhmad Sulthoni; Akhmadiyah Saputra (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study explores the concept of women's deception in the stories of Prophet Yusuf and Prophet Sulaiman, based on a thematic interpretation in Tafsir al-Mishbah by M. Quraish Shihab. The research focuses on two prominent female figures: Zulaikha and the Queen of Sheba, each representing different forms of deception within their respective contexts. Utilizing a library research method with a tafsir maudhū’i (thematic exegesis) approach, the study aims to examine the verses of the Qur’an in a contextual and comprehensive manner. The findings reveal that Quraish Shihab does not generalize women negatively, but instead interprets their actions based on their social and psychological background. Zulaikha’s behavior is portrayed as personal temptation, while Queen Balqis’s strategy is framed as a form of diplomatic intelligence. Tafsir al-Mishbah presents a fair, humanistic, and contextual interpretation that not only addresses theological aspects but also emphasizes the practical application of Qur’anic values in social life. This study affirms the importance of a balanced and profound approach in understanding women’s roles as depicted in the Qur’an.